2023
DOI: 10.1186/s12915-023-01521-5
|View full text |Cite
|
Sign up to set email alerts
|

Human Satellite 1A analysis provides evidence of pericentromeric transcription

Abstract: Background Pericentromeric regions of human chromosomes are composed of tandem-repeated and highly organized sequences named satellite DNAs. Human classical satellite DNAs are classified into three families named HSat1, HSat2, and HSat3, which have historically posed a challenge for the assembly of the human reference genome where they are misrepresented due to their repetitive nature. Although being known for a long time as the most AT-rich fraction of the human genome, classical satellite HSa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 121 publications
0
10
0
Order By: Relevance
“…Misregulation of satDNA expression can lead to various abnormalities in the genomic architecture, chromosome segregation and gametogenesis. Changes in copy number of satDNAs and their transcription rates may be associated with stress, environmental adaptations and pathological states, such as oncogenic transformation [ 18 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Functional Importance Of Satellite Dnas and Partnership With...mentioning
confidence: 99%
“…Misregulation of satDNA expression can lead to various abnormalities in the genomic architecture, chromosome segregation and gametogenesis. Changes in copy number of satDNAs and their transcription rates may be associated with stress, environmental adaptations and pathological states, such as oncogenic transformation [ 18 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Functional Importance Of Satellite Dnas and Partnership With...mentioning
confidence: 99%
“…The copy numbers of HSat1 DNA monomers in the genome are also highly variable, but little correlation between genomic copy numbers and RNA expression levels has been detected. Physical mapping of HSat1 lncRNA in the human chromosomes by FISH revealed clear FISH signals in all acrocentric chromosomes and chromosomes 1 and 3 (Lopes et al , 2023 ). RNA‐FISH showed that HSat1A transcripts exhibit cluster‐like organization in the nucleus, albeit with distinct signal patterns in different cell lines.…”
Section: Hsat1 Lncrnamentioning
confidence: 99%
“…A summary of features and functions of satellite RNAs.There had long been a lack of studies on the transcripts from HSat1 regions, but recentlyLopes et al (2023) extensively characterized the expression and intracellular localization of transcripts from HSat1A regions, which are located mostly on chr3, chr4, and chr13. HSat1 expression levels vary markedly in various cancer cell lines and human tissues.…”
mentioning
confidence: 99%
“…Despite the initial ideas about transcriptionally silent pericentromeres, we know now that the DNA of all HSAT families (HSAT1-3) can be transcribed in a cell under certain circumstances (stress, malignization, cancer-associated polarization, differentiation, senescence, oogenesis, and embryogenesis) [ 19 , 25 , 41 , 42 , 43 ]. In cancer cells, HSAT DNA and RNA contribute to genetic instability [ 20 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%